2019
DOI: 10.1111/ffe.12995
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in fibre metal laminates: The interplay between fatigue in metals and fatigue in composites

Abstract: With the introduction of fibre metal laminates (FMLs) as a (fatigue) damage tolerant material concept in aeronautics, an interesting field emerged where fatigue damage interaction plays a dominant role. The hybrid concept effectively demands evaluating fatigue damage growth based on fracture phenomena typical for both metals and fibre‐reinforced composites that continuously interact with each other. This paper explains current understanding of the fatigue fracture phenomena in FMLs, and it demonstrates how thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Glass-reinforced aluminium, known as GLARE, is a fibre metal laminate (FML) consisting of alternating S2-glass/FM94-epoxy composite plies and 2024-T3 aluminium layers. Panels made of GLARE FMLs are hybrid composites that offer higher damage tolerance characteristics and lower specific mass than monolithic aluminium panels, the reason why they have gained interest from the aerospace industry and have seen widespread applications, especially on the Airbus A380 fuselage and empennage-leading edges [31][32][33]. Figure 5 shows an X-ray CT image of a GLARE 3-4/3 specimen with impact damage acquired using the GE Phoenix v|tome|x M system.…”
Section: Impact Damagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass-reinforced aluminium, known as GLARE, is a fibre metal laminate (FML) consisting of alternating S2-glass/FM94-epoxy composite plies and 2024-T3 aluminium layers. Panels made of GLARE FMLs are hybrid composites that offer higher damage tolerance characteristics and lower specific mass than monolithic aluminium panels, the reason why they have gained interest from the aerospace industry and have seen widespread applications, especially on the Airbus A380 fuselage and empennage-leading edges [31][32][33]. Figure 5 shows an X-ray CT image of a GLARE 3-4/3 specimen with impact damage acquired using the GE Phoenix v|tome|x M system.…”
Section: Impact Damagesmentioning
confidence: 99%
“…However, delaminations distribute high stresses over a large area, which allows the bridging fibres to remain intact and contributes to the crack bridging. Epoxies, which are very tough and have high delamination resistance, result in premature fibre failure, further reducing the fatigue life, which has been commonly observed in metals [31]. It has been reported in experimental studies that delaminations only occur at interfaces between plies with different fibre orientations under impact [34].…”
Section: Impact Damagesmentioning
confidence: 99%
“…3 The initial intention of developing FMLs was to enhance fatigue resistance; however, it was identified that FMLs possess other superior characteristics over metallic alloys. 4 Owing to their lightweight and high damage tolerance properties, energy efficiency within the transportation sector could be drastically improved without compromising safety performance. The development of FMLs is associated with the poor fatigue performance of metallic alloys and weak damage tolerance of fibre reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wu and Yang GLARE shows 10 to 100 times slower crack growth rates compared to Aluminium [2]. The fatigue failure in FMLs, as described by Alderliesten [3], begins with crack initiation and propagation under cyclic loading in a metallic layer followed by delamination between the metal and composite interface. The delamination distributes the stress caused by the cyclic loading over a larger area which decreases the stress in the composite layers and decreases the risk of composite failure i.e.…”
mentioning
confidence: 99%
“…(matrix cracking or fibre splitting) [4]. Therefore, the fibres remain intact and allow the load to be transferred through the composite layer across the crack [3]. This is often referred to as the bridging mechanism, where it plays a significant role in decreasing the crack growth in FMLs.…”
mentioning
confidence: 99%